Visual search strategies of young soccer players according to positional role - Dambroz, Felipe (2022)
We aimed to compare the visual search strategies of young soccer players with different positional roles. Data was collected with the Mobile Eye Tracking — XG to verify gaze behaviour through visual focus. At the laboratory, an 11-a-side match play video-based soccer simulation from a third-person perspective was presented to the participants. Players were grouped according to their positional roles: defenders (n= 6), midfielders (n= 6) and forwards (n= 5). Visual search strategies were classified according to five fixation locations: "player in possession", "ball", "teammates", "opponents" and "space". The number of fixations and the fixation duration in each location was assessed. One-way ANOVA was performed to compare mean values. Midfielders and forwards showed significant differences in the number of fixations (15.50± 5.85 vs. 27.80± 7.36; p= 0.023) and fixation duration (8.00± 3.11 secs vs. 20.10± 8.47 secs; p= 0.016) for the category "ball", as well as in the number of fixations (22.00± 5.62 vs. 34.60± 1.81; p= 0.044) for "teammates". No other differences were observed. We concluded that the positional role was not relevant to the visual search strategy adopted by young soccer players. This finding is important for coaches and researchers to understand the cognitive and perceptual skills of young soccer players. It can also help coaches design specific training with appropriate stimuli for the players'  development.